Effect of Asbuton Type B50/30 and Oil Asphalt Variation on AC-WC Mixture Using Marshall Method - Rahmawati Rahmawati; Hakzah Hakzah; Hendro Widarto (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2025)
Asbuton is a promising local material that can partially replace petroleum asphalt in AC-WC hot mix asphalt. This study aims to investigate the influence of varying Asbuton B50/30 content on the performance of asphalt mixtures using the Marshall method. The optimum asphalt content (OAC) was determined to be 6.29%, followed by testing with Asbuton contents of 7%, 9%, and 11% of the total asphalt weight. The evaluated parameters included stability, flow, Marshall Quotient (MQ), and volumetric properties (VIM, VMA, and VFB), all assessed against Bina Marga technical specifications. The results indicate that 7% Asbuton content provides the best performance, yielding the highest stability (1977.70 kg) and MQ (632.35 kg/mm), while maintaining volumetric parameters within specification limits. At higher Asbuton contents (9% and 11%), stability and MQ declined, whereas flow and VFB increased, suggesting an over-binder effect that reduces structural integrity. These findings highlight the importance of proper Asbuton dosage control to balance mechanical and volumetric properties. This study contributes to the advancement of knowledge in asphalt pavement engineering by emphasizing the dual role of Asbuton as both a filler and a binder modifier, while also providing a scientific basis for utilizing local materials to support more sustainable pavement development.